Global disease burden of inflammatory bowel disease in women and women of childbearing age from 1990 to 2021 and its prediction to 2040 - Jiefeng Zhao; Daxing Miao; Tianbao Xiao; Tao Yang; Jiang Chen; Xiangquan Lai (PLoS ONE, 2025)
Objective The incidence of inflammatory bowel disease (IBD) peaks between the ages of 15 and 40. This age range coincides with women of childbearing age (WCBA), who face unique challenges like adverse pregnancy outcomes and heightened anxiety. Despite the rising global prevalence of IBD, particularly among younger populations, the burden of IBD among women, especially WCBA, remains underexplored. Methods This study utilized data from the Global Burden of Disease (GBD) Study 2021 to examine the prevalence, disability-adjusted life-years (DALYs), and mortality of IBD among women and WCBA from 1990 to 2021. The estimated annual percentage change (EAPC) in age-standardized (AS) rates was calculated to quantify temporal trends. The relationship between the socio-demographic index (SDI) and AS prevalence, DALYs rate, and mortality was assessed using methodologies such as the slope index of inequality, concentration index, frontier analysis, decomposition analysis, and the Bayesian Age-Period-Cohort model. Results From 1990 to 2021, a significant global decline was observed in the AS prevalence rate (ASPR), DALYs rate (ASDR), and mortality rate (ASMR) of IBD among women. For WCBA, the global prevalence rate decreased slightly, while the DALYs rate increased slightly, and mortality remained unchanged. Significant variations in trends were noted across different SDI and GBD regions. In 2021, the highest ASPR, ASDR, and ASMR for female IBD were reported in Australasia, high-income North America, and Western Europe, respectively. The most pronounced upward trends were observed in East Asia, Australasia, and high-income North America. China, Mauritius, and Kuwait experienced the most significant increases in prevalence, DALYs, and mortality rates among WCBA. Health inequalities across socioeconomic strata decreased, but substantial gaps remained, particularly in India. Conclusion This study reveals a global decline in the burden of IBD among women and WCBA from 1990 to 2021, with notable regional disparities. The decreasing trends highlight the effectiveness of certain interventions and improvements in healthcare. However, the increasing burden in some regions and for certain age groups, along with significant gaps identified in frontier analysis, emphasize the need for targeted public health strategies and resource allocation to further reduce the burden of IBD among women and WCBA.